Bacterial Uropathogens and Their Antimicrobial Susceptibility Profiles among Symptomatic UTI Patients Attending Major Healthcare Facilities in Calabar, Southern Nigeria - Sylvanus Akpak Upula; Emmanuel Effiong Bassey; Edet E. Ikpi (International Journal of Pathogen Research, 2026)
Background: Urinary tract infections (UTIs) are a major global health concern, affecting millions of individuals annually. Their management is increasingly challenged by the growing prevalence of antimicrobial resistance among uropathogens. Aim: This study aimed to determine the prevalence and multidrug resistance (MDR) profile of bacterial uropathogens isolated from symptomatic UTI patients attending Major healthcare facilities in Calabar, Nigeria. Methods: A total of 65 bacterial uropathogens were isolated from symptomatic UTI patients attending Major healthcare facilities in Calabar. The isolates were identified using standard microbiological techniques, while Gram-negative isolates were further confirmed using commercial biochemical identification kits, including Analytical Profile Index (API) 20E and API 20NE (bioMérieux). Antimicrobial susceptibility testing was performed using the modified Kirby–Bauer disc diffusion method in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Klebsiella pneumoniae was the most frequently isolated pathogen (23.1%), followed by Staphylococcus sp. (16.9%) and Escherichia coli (12.3%). Other organisms identified included Enterobacter cloacae, Citrobacter freundii, Proteus mirabilis, Serratia marcescens, Pseudomonas aeruginosa, Cronobacter sp., Enterococcus sp., Citrobacter koseri, and Pseudomonas luteola. High levels of resistance were observed among the isolates to augmentin, amoxicillin, septrin, ampiclox, erythromycin, and rifampicin. Conversely, relatively higher susceptibility to levofloxacin, gentamicin, ciprofloxacin, and sparfloxacin was observed. Conclusion: The findings provide current evidence on the distribution of bacterial uropathogens and the burden of MDR among UTI patients attending Major healthcare facilities in Calabar, Nigeria. The observed resistance patterns highlight the importance of local antimicrobial susceptibility surveillance to guide appropriate empirical treatment of UTIs. Prudent and evidence-based use of antimicrobial agents is recommended to limit the emergence and spread of antimicrobial resistance among bacterial uropathogens.